2020
DOI: 10.1136/annrheumdis-2020-219522
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on ‘Incidence trend of five common musculoskeletal disorders from 1990 to 2017 at the global, regional and national level: results from the global burden of disease study 2017’

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…2 For exact occupations, it is unfortunately impossible to divide patients with musculoskeletal (MSK) disorders into groups according to their occupations since there are no corresponding estimates from the Global Burden of Disease study 2017. 3 4 We agree with your comments on effects of social risk factors and occupational risks between high and low human development index (HDI) countries 1 ; in our study, a stable or increasing trend of age-standardised incidence rate (ASR) for low back pain (LBP) was observed. 2 However, occupational risks attributable to ASR might be more likely to be modified among countries and territories with higher HDI.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…2 For exact occupations, it is unfortunately impossible to divide patients with musculoskeletal (MSK) disorders into groups according to their occupations since there are no corresponding estimates from the Global Burden of Disease study 2017. 3 4 We agree with your comments on effects of social risk factors and occupational risks between high and low human development index (HDI) countries 1 ; in our study, a stable or increasing trend of age-standardised incidence rate (ASR) for low back pain (LBP) was observed. 2 However, occupational risks attributable to ASR might be more likely to be modified among countries and territories with higher HDI.…”
supporting
confidence: 68%
“…You indicated that Taiwan's HDI in 2019 was 0.911. 1 We are not sure of its comparability with the other data from the Human Development Report. Moreover, we need data in 1990 and 2017.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…IVDD not only causes great suffering to the lives and spirits of patients, but it also places a heavy financial burden on those individuals, their families, and the entire nation. [3] Patients with IVDD are currently treated mostly with 2 forms of conservative and surgical ways. Physical therapy and medications can help early-stage IVDD patients with their long-term pain, but they cannot address the underlying causes of the disease or its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of arthritis is ∼0.34% to 0.36% 1–3 . The most common types of arthritis are osteoarthritis (OA), rheumatoid arthritis (RA), psoriatic arthritis (PsA), and gouty arthritis (GA).…”
mentioning
confidence: 99%